Forensic Stylistics in Genre-Based EFL Academic Writing: Linguistic Evidence of Authorship - Asbar Asbar; Samsudin Samsudin; Umiyati Jabri; Nurmin Solli (GLENS: Global English Insights Journal, 2026)
Verifying authorship in student academic writing remains a major challenge in higher education, particularly because plagiarism-detection systems primarily measure text similarity rather than linguistic identity. This study investigates linguistic evidence of authorship in EFL academic writing by integrating forensic stylistics and genre analysis. Using a descriptive qualitative design, the study analysed 56 essays written by 28 undergraduate EFL students in the English Education Department at Universitas Muhammadiyah Enrekang across two writing tasks. The analysis focused on lexical clusters, syntactic constructions, punctuation patterns, and genre staging to identify consistency in authorial style. The findings show that 75% of participants demonstrated stable stylistic fingerprints, while 71% maintained consistent genre realization across essays, indicating that authorial style tends to persist alongside genre mastery. In contrast, 25% of participants displayed stylistic and schematic discontinuities suggesting potential non-authentic authorship, whereas 7% showed inconclusive patterns. These findings suggest that combining forensic stylistics and genre analysis offers a more reliable approach to authorship verification than similarity-based plagiarism detection. This implication becomes increasingly relevant in response to emerging challenges in digital academic writing, including the growing use of digital writing assistance and outsourced academic work.